2021
DOI: 10.1155/2021/8831867
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Takayasu’s Arteritis in Patients with Inflammatory Bowel Diseases

Abstract: Background. Takayasu’s arteritis (TA) and inflammatory bowel disease (IBD) are chronic inflammatory granulomatous disorders that have rarely been concomitantly reported in case reports and small case series. Objective. We report a series of seven cases of TA and IBD association in two referral centers with a comprehensive review of literature. Methods. We analyzed retrospectively the electronic medical charts of TA-IBD patients at the University Hospital of São Paulo, Brazil, and at the Sheba Medical Center at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…Human lymphocyte antigen (HLA) B52 is known to be a common genetic background between TA and UC (3) but not between TA and CD. Akiyama et al reported that the endoscopic features of IBD complicated with TA at the initial diagnosis showed discontinuous and focal mucosal inflammations (87.5%), leading to a typical distribution of UC subsequently in many cases (4), and it was reported that many patients developed IBD first, followed by TA subsequently (10,11). These clinical characteristics and HLA type were all compatible with the present case.…”
Section: Discussionsupporting
confidence: 85%
“…Human lymphocyte antigen (HLA) B52 is known to be a common genetic background between TA and UC (3) but not between TA and CD. Akiyama et al reported that the endoscopic features of IBD complicated with TA at the initial diagnosis showed discontinuous and focal mucosal inflammations (87.5%), leading to a typical distribution of UC subsequently in many cases (4), and it was reported that many patients developed IBD first, followed by TA subsequently (10,11). These clinical characteristics and HLA type were all compatible with the present case.…”
Section: Discussionsupporting
confidence: 85%
“…Миксоматозная дегенерация (система IL-33/ST2 может участвовать в развитии миксоматоза путем усиления ремоделирования внеклеточного матрикса) [35] Артериит Такаясу. Преимущественно у женщин с БК Генетические факторы риска: носительство человеческих лейкоцитарных антигенов HLA-A, HLA-B52, HLA-B35, HLA-DRB-1, HLA-DRB-2, обусловливаю щих совместно развитие ВЗК и артериита Такаясу [36] Примечание.…”
Section: вальвулопатииunclassified